Kurikulum dan Dinamika Perubahannya di Pondok Pesantren Universitas Islam Indonesia Yogyakarta. - shofa, rizka amalia (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
This paper is intended to express the concept and dynamics of curriculum change of Pondok Pesantren Universitas Islam Indonesia. The importance of the problem discussedis related to curriculum that is used by Pondok Pesantren as one of the foundations ofthe development of Islamic educational institutions that would potentially affect thedevelopment of Islamic education in Indonesia in general. The concept of curriculumwhich is applied does not follow the national curriculum that is used at school or college.The result of the research showed that there is a change in the destination and settingof the curriculum of Pondok Pesantren Universitas Islam Indonesia that referred toUniversitas Islam Indonesia’s aim to be World Class University. The change affectedthe content of the curriculum, teaching materials, and the learning methods. A changeimpact on the activity of students who are not only prepared to be a mujtahid , but moregeared to hone the ability of thinking and researching .